Students’ Speaking Problems: A Case Study of Chemistry Students at UPI Bandung - Nugraha, Andrie Sukma; Putra, Juang Rudianto (ENGLISH JOURNAL, 2016)
International schools require teachers of mathematics and science to teach in English. The problem is that not all teachers of the schools have the ability to speak in English. For that reason, institutions that accommodate future teachers should have concern on this issue especially the mathematics and science department. The chemistry department in UPI realizes the issue and has sent their students to teach in internationals schools around Bandung and Bogor for their teaching practice (PLP).The main purpose of the research is to identify speaking problems that international class students of the Chemistry Department in UPI have. Additionally, the result of this present research is also expected to provide valuable suggestion for the consideration of English course designers in designing future English course. Observation and the distribution of questionnaire help provide the data. The results of the research show that the main problems that the students face in speaking are diction issues, pronouncing words with English sounds that do not exist in Bahasa Indonesia, and speaking according to grammatical rules. Meanwhile, findings regarding suggestions of the respondents for future English courses show that the respondents prefer both native and non-native speakers in class, the instructor to act as a teacher and speaking partner, a situation where students talk more, materials in the form of visual aids, English for teaching and English for chemistry to dominate the content of the course, activities in the form of discussion and games, and an evaluation in the form of both oral and written test. As a suggestion, future English course designers should pay attention to the problems that students have in speaking and also to identify what and how students want to learn in an English Course before designing a course as knowing what students know and do not know will provide a more effective and useful training for the targets